Some Ecological Issues In a Few Luigi Pirandello's Short Stories1 - Mihaljevic, Nikica (Mediterranean Journal of Social Sciences, 2012)
The research starts from the theory of environmental literary criticism and it uses its methodology in the analysis ofsome Luigi Pirandello's short stories. In a literary text, the ecocriticism analyzes the hierarchical order imposed by the centennialdictatorship of some members of the „vertical“ society. This order also inevitably includes some outcast elements which becomemarginalized by the policy of centralism, and the ecocriticism methodology permits the reader to concentrate on these elements.If we try to conceive the concept of the world not exclusively anthropocentric, it means that a man should interact with the nature,which will lead to the horizontal vision of the society. In this work the focus is on the Pirandello's characters which are describedas marginalized, exposed to the atrocities of the social and moral extermination. These characters are assigned the roles ofvictims, since subject to the discriminatory mechanism. The analysis aims to research whether in Pirandello's texts it is possible,by applying the ecocritical methods, to regain the balance among the characters and to equalize all the members of „Pirandello'sliterary society“.